Sistem Pakar Tes Kepribadian Menggunakan Metode Dempster-Shafer - Sri Wahyuni Sinaga (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2021)
Personality is a pattern of human behavior that comes from within someone's self. personality sometimes needs to be adapted to the context in the world of employment, personality is often identified with the attitude and character of someone in the world of work and everyday life. Women who are considered to have a good personality can be seen from the way he walks, how to speak, and how to behave properly. The term personality comes from the Latin word "persona" which means mask or mask, which is the face cover which is often used by stage players, whose purpose is to describe a person's behavior, character, or personality. Some types of personality based on big five personality personality are classified into several types of personality, namely: Neuroticism, Extraversion, Openness To Experience, Conscientiousness, Agreeableness. Expert systems are computer-based systems that use knowledge, facts, and reasoning techniques in solving problems that can usually only be solved by an expert in a particular field. Expert systems provide added value to technology to help experts determine a person's personality based on the characteristics and characteristics of individual eating to need to be studied again with certain methods. Dempster shafer method - is an expert system method used by experts (experts) to determine relevant and accurate decisions. by applying the dempster shafer method to the expert system the personality test can determine the type of individual or individual servitude based on each characteristic so that it can be based on the type of personality.